Synthesis of Poly(Vinylbenzyl Chloride) (PVBC) and temperature effect - Fatin Athilia Aidi Zameri, 1995-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2018